What's up with the self-employed? A cross-national perspective on the self-employed's work-related mental well-being - Jessie Gevaert; Deborah De Moortel; Mathijn Wilkens; Christophe Vanroelen (Elsevier, 2018)
Although many governments actively stimulate self-employment, their work-related mental well-being remains understudied. The aim of current study is to investigate the mental well-being of different types of self-employed, testing whether mental well-being differences among self-employed are explained by the presence of work characteristics that are in accordance with the ideal-typical image of the "successful entrepreneur" (e.g. creativity, willingness to take risks, innovativeness, high intrinsic motivation, skilfulness and the ability of recognizing opportunities). Moreover, we investigate the relation of country-level "entrepreneurial climate" and the individual mental well-being of self-employed. For this purpose, data from the European Working Conditions Survey, round 6 (2015) was analysed, including 5448 cases, originating from the 28 EU-member states. Multilevel random intercepts modelling was used to investigate associations of both individual- and country-level characteristics with mental well-being. We found that motivation, the ability to recognize opportunities, and finding it easy to be self-employed positively influences the mental well-being of self-employed. Respondents with these characteristics are often medium-big employers, while farmers, dependent freelancers and own account workers generally have less of these features and tend to have lower levels of mental well-being. At the country-level, positive entrepreneurship perception relates to more advantageous mental health scores in self-employed. These results implicate that policies promoting self-employment should be (more) concerned with the work-related characteristics of (future) self-employed. Keywords: Self-employment, Mental well-being, Cross-national, Entrepreneurial characteristics, Entrepreneurial ecosystems, EU 28